Probable REM Sleep Behavior Disorder Is a Risk Factor for Symptom Progression in Parkinson Disease - Barasa, Ashley; Wang, Jijia; Dewey, Richard B. (Frontiers in Neurology, 2021)
Background The literature is conflicting on whether rapid eye movement sleep behavior disorder (RBD) is associated with more rapid progression of Parkinson disease (PD). Objective We aimed to determine 1) how stable probable RBD (pRBD) is over time and 2) whether it predicts faster PD progression. Methods We evaluated participants in the Parkinson’s Disease Biomarker Project who were prospectively assessed every 6-12 months with a series of motor, non-motor, disability, and health status scales. For aim 1, we calculated the incidence and disappearance rates of pRBD and compared stability of pRBD in PD with control subjects. For aim 2, we developed multiple regression models to determine if pRBD at baseline influenced the rate of change or average value at 48 months of 10 outcome variables. Results We found that pRBD was a less stable diagnosis for PD than controls. In pRBD+ subjects, MDS-UPDRS part III score progressed 2.78 points per year faster (p<0.01), MDS-UPDRS total score progressed 3.98 points per year faster (p<0.01), a global composite outcome worsened by 0.09 points per year faster (p=0.02), and PDQ-39 mobility score progressed 2.57 percentage points per year faster (p<0.01). Average scores at 48 months were 8.89 (p=0.02) and 14.3 (p=0.01) points higher for pRBD+ in MDS-UPDRS part III and total scores respectively. Conclusions Our study confirms that pRBD detected at the start of a study portends more rapid progression of PD. Knowing this could be useful for enriching clinical trials with fast progressors to accelerate discovery of a disease modifying agent.